Peran Pemerintah dalam Pengembangan Sistem Penyediaan Air Minum (SPAM) Berbasis Pembangunan Berkelanjutan: Kajian Literatur - Minson Simatupang; La Ode Ichwan Sjachrawy; Abdul Kadir; Try Sugiyarto Soeparyanto (Journal of Science, Technology, and Innovation, 2026)
This study aims to analyze the government’s role in the development of a drinking water supply system based on sustainable development through a literature review. The method used is a narrative integrative review with thematic synthesis of reputable national and international journals discussing drinking water governance, public policy, and infrastructure sustainability. The results of the study indicate that the government’s role encompasses regulatory functions, institutional strengthening, and facilitating multi-stakeholder collaboration in the provision of drinking water services. The sustainability of the WSS is influenced by policy synchronization, financing effectiveness, community participation, and technological innovations in water distribution. The findings also indicate implementation gaps resulting from weak planning integration and limited institutional capacity at the local level. This study emphasizes that WSS development depends not only on physical infrastructure but also on adaptive and collaborative governance. This research makes a conceptual contribution to strengthening a sustainability-based WSS governance model and offers an analytical framework for the development of more integrated drinking water policies.